Market orientation and corporate success: Findings from Germany - Wolfgang Fritz; Norbert Mundorf (Technische Universität Braunschweig, Institut für Marketing, 1994)
The significance of the markteing concept for corporate management is the subject of a long-standing controversy. This empirical study conducted in Germany, the largest European market, shows that together with other basic dimensions of management, market orientation contributes substantially to corporate success. In addition, the results indicate that popular practical measures designed to implement the marketing concept within the organization may cause negative side effects on corporate success. These risks could be controlled by observing a number of strategies suggested in this article. But detecting these risks requires a holistic research approach to corporate management, of which market orientation represents only one basic dimension. An integrated perspective of research, such as the one presented in this paper, is still alien to the empirical research regarding the question of whether market orientation exerts an impact on corporate success.
Keywords: 650